Islamic economics and finance : a glossary - Khan, Muhammad Akram; Khan, Muhammad Akram (London ; New York : Routledge, 2003)
This glossary, fully updated and revised for the new edition, uses easy-to-understand language to introduce terms used by Muslim scholars, historians and legal experts. The book covers terms from Arabic, Urdu, Turkish, Malaysian and English sources, while covering the Islamic side of terms such as taxation, banking, insurance, accounting and auditing." "The book will appeal to economists, bankers and accountants, as well as students and researchers with an interest in economics and finance.
Rev. ed. of: Glossary of Islamic economics. London ; New York : Mansell, 1990.
Includes bibliographical references and index.
oif 15/10/15
Loans
Keywords: Economics - dictionary; Economics - religious aspects; Arabic language - dictionaries